A comparison of the peers method and traditional methodologies, and risk behaviors in studies of the prevalence of drug consumption in a population of female, chilean students - Rodríguez T., Jorge; Fernández, Ana Maria; Valdés C., Macarena; Hernández A., Enrique; Ramírez P., Sergio; Román Q., América (The Spanish Journal of Psychology, 2008)
The present study investigates drug consumption and risk behaviors among female students between 8th and 12th grade in two communities in the city of Santiago, Chile. Based on studies of university populations, we hypothesize that the students’ reports of their consumption of licit drugs will tend to be consistent with their actual use of said drugs using two methods to investigate consumption, while their consumption of illicit drugs will be susceptible, and will tend to be under reported when evaluated through traditional self-report measures. In order to compare the two methods, a cross-sectional study was designed that would compare reported drug consumption, first using the peers method, and then by means of traditional self-report in a group of 350 students. The results show that women’s reports of licit drug consumption converge using the two methods, while as earlier suggested, women’s illicit drug consumption was found to be under reported when traditional methodologies were used.